Exotic Spices in Flux: Archaeobotanical Material from Medieval and Early Modern Sites of the Czech Lands (Czech Republic) - Preusz, Michal; Kodýdková, Kateřina; Kočár, Petr; Vaněček, Zdeněk (Archeologické centrum Olomouc, 2015)
According to the core-periphery model of economic geography, the Medieval and Early Modern Czech lands can be called a semi-periphery. They are located in a hilly part of central Europe, in the shadows of the world’s naval powers. Over the centuries this location has greatly influenced their domestic consumer society, in many ways lacking in self-sufficiency and often having to rely on the import of foreign and exotic goods through a global sales network; amongst these rare goods were different kinds of spices. These imported species, specifically assimilated, became not only an important part of the diet, but also a symbol of luxury. This paper presents the current state of research into exotic spices that have been discovered in archaeological contexts in today’s Czech Republic, and illustrates their importance for the interpretation of trade in exotic goods and the historical socio-cultural level of local consumers.
Keywords: exotic spices, luxury food, imports, New World, Asia, Europe, trade routes, consumer society, archaeobotany, macro-remains